Nascer em Belo Horizonte: análise da relação entre a estrutura das maternidades e os indicadores obstétricos e perinatais - Lorena Marcia de Freitas Marques Nacif (2016)
The quality of heath services is an important study field and has become a necessity for both public and private health systems. In Brazil the implementation of a formal and programmed system to evaluate the quality of health services is still incipient. Over the last decade, the city of Belo Horizonte has invested to improve pregnant and newborn health care network. However, we can still observe several unsatisfactory obstetric indicators and care failures, mainly related to the pregnantadmission in the maternity hospital and attendance during labor and childbirth. This work presents an ecological study that analyzes maternity hospitals structures in the city of Belo Horizonte, Minas Gerais state and its relation to the obstetric and perinatal indicators. The data used in this study was generated by the research project Birth in Belo Horizonte: inquiry about labor and birth performed in public and private maternity hospitals in the city of Belo Horizonte between november, 2011 andmarch, 2013. The study has been performed in 11 out of 14 city maternity hospitals during the year of 2011. Seven institutions of this study are public and four are private. In the first part of this study we have performed data exploratory analysis based on descriptive statistics in order to characterize the hospital institutions. Then we propose a maternity adequation index based on what is defined in the current legislation and using the Principal Components Analysis (PCA) statistical technique.The global adequation index for each maternity hospital was associated to the obstetric and perinatal indicators and four other indicators that are related to best practices in maternity health care and neonatal outcomes. Results: We show that high maternity hospital adequation indexes are associated to high cesarean sections and epidural analgesia rates. We also show that the best practices during labor, childbirth and related to the newborn are more often observed in maternity hospitalswith smaller global structure adequation indexes and in public institutions where the midwife was taking part in the labor. The Apgar index smaller than seven on the fifth minute after birth and adverse neonatal outcomes are also associated to higher global structure adequation indexes. Conclusion: Although the city of Belo Horizontehas shown several advances in the pregnant and newborn health care services, the investments and structure improvements are not sufficient to achieve satisfactory indexes. Structure adequation has certainly a positivel impact in maternity health care servives. However, this study suggests that in order to achieve higher indicators we should still certify a good structure in health care instituitions. The focus of thisimprovement should be in the challenges that were evidenced by inadequacies that were found such as care and operational resources.